Basic Accounting Learning Innovation with a Business Coaching Approach - Siswandari; Susilaningsih; Sohidin; Binti Muchsini; Jaryanto; Nurhasan Hamidi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Community Service Activities for Basic Accounting Learning Innovation with a Business Coaching Method Approach involves business coaching practices for teachers of accounting and finance professional programs, to show ways that learning models can be applied with fun methods, a comfortable atmosphere, and encouraging students to be active and responsive to the material presented by the teacher. The partner in this activity is the MGMP of Accounting Teachers in Boyolali Regency, Central Java. The solution provided is business coaching for teachers of MGMP Accounting Teachers in Boyolali Regency. The objectives of this activity are to improve accounting teachers' understanding of accounting products, to improve teachers' ability to design accounting products, to use computers for designing accounting products, to use spreadsheets as a tool, and to encourage teachers to collaborate with workplace partners in assessing accounting product needs. The benefits of this activity include increased teacher competence in accounting and finance subjects. Implementing the service is through five stages: conducting pre-tests, training in business coaching methods, mentoring, monitoring and evaluation, and reporting. This activity increases the competence of subject teachers in accounting and finance programs in developing various learning methods for accounting subjects by the requirements of the Merdeka Curriculum, so it is hoped that students can better understand accounting practices in the business world.